POLITICAL MYTHS AND STEREOTYPES IN THE ETHNIC CONSCIOUSNESS OF THE CHUVASH PEOPLE - S. Grishaeva (Вестник университета, 2019)
Theoretical and methodological basis of the study of political myths and stereotypes is studied, their role and influence on the modern life of the Chuvash Republic are analyzed. Classification of archetypes of the Chuvash people within the concept of C. G. Jung is given. The history and current state of political myths and stereotypes in the ethnic consciousness of the Chuvash people are studied. Interpretation of the state symbols of the Chuvash Republic is given. The different political interpretations of the past and present of the Chuvash Republic are examined.